Structure and regeneration capacity of a urban forest fragment - doi: 10.4025/actascibiolsci.v35i2.14810 - Débora Cristina Souza; Arielle Vanessa Barbosa Alves; Luciana Oliveira Tolomeotti; Jilvan Ribeiro da Silva; Janaina de Melo Franco (Acta Scientiarum: Biological Sciences, 2012)
Understanding the plant communities affected by human activities related to urbanization is an important tool to conserve these. In this way, this study on an urban forest fragment aimed to evaluate, through a phytosociological study and investigation of the germination of the seed bank, the current forest structure, the successional strata, and the regenerative capacity of the remnant. Three different stages comprised this research, the first with a floristic survey of the entire forest remnant, then the phytosociological study of the canopy (PAP above 10 cm) and regeneration strata (PAP 5-10 cm), and at last, the study on the seed bank. The phytosociological survey of the canopy stratum presented 1,368 individuals, with 41 species distributed into 24 families. The stratum of natural regeneration had 665 individuals, being 38 species distributed into 24 families. The seed bank was made up by only 8 native species, and 3 exotic species. The floristic diversity of the seed bank in all samples was low due to few species provide seeds to the soil. In addition, the strata and the seed bank had a low similarity, confirming thus the fragility and the need for preservationist attitudes.